Pteridophyte Diversity in Hirpora Wildlife Sanctuary, Shopian, Kashmir Valley, Jammu and Kashmir - Mir, Shakoor Ahmad; Mishra, Anand Kumar; Reshi, Zafar Ahmad; Sharma, Maheshwar Prasad (Indian Forester, 2017)
Based on the survey and collection between 2010 - 2012 from Hirpora Wildlife Sanctuary, Shopian, Jammu and Kashmir in present communication vascular cryptograms growing in the sanctuary are documented. A total 46 species of ferns and fern-allies belonging 20 genera and 9 families were recorded. Among them Dryopteridaceae (14 species and 2 genera) was the dominant family followed by Woodsiaceae (12 species and 6 genera), Aspleniaceae (8 species and 1 genera) and Pteridaceae (6 species and 5 genera). The dominant genera collected from the sanctuary were Dryopteris and Asplenium (8 species each) followed by Polystichum (6 species) and Athyrium (4 species). All the ferns and fern allies, along with recent nomenclature, habit, habitat, status and exsiccata have been provided here in tabular form.